2018
DOI: 10.1186/s12970-018-0224-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-alanine supplementation during a 5-week strength training program: a randomized, controlled study

Abstract: Backgroundβ-Alanine (BA) is a non-essential amino acid that has been shown to enhance exercise performance. The purpose of this investigation was to determine if BA supplementation improved the adaptive response to five weeks of a resistance training program.MethodsThirty healthy, strength-trained individuals were randomly assigned to the experimental groups placebo (PLA) or BA. Over 5 weeks of strength training, subjects in BA took 6.4 g/day of BA as 8 × 800 mg doses each at least 1.5 h apart. The training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Thus, it has been demonstrated that B-alanine supplementation, in combination with creatine, increases the training load and levels of lean mass with respect to the exclusive intake of creatine [45]. Furthermore, it has recently been reported that supplementation with BA increases both 1 RM and the maximum power levels at 1 RM loads and maximum power levels after a period of supplementation in combination with resistance training [46]. In the same way, sodium bicarbonate supplementation improves extracellular pH regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been demonstrated that B-alanine supplementation, in combination with creatine, increases the training load and levels of lean mass with respect to the exclusive intake of creatine [45]. Furthermore, it has recently been reported that supplementation with BA increases both 1 RM and the maximum power levels at 1 RM loads and maximum power levels after a period of supplementation in combination with resistance training [46]. In the same way, sodium bicarbonate supplementation improves extracellular pH regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whereas Williams et al [113] assessed muscle power and velocity during two single explosive repetitions with full recovery (5 min rest between sets), Ranchal-Sánchez et al [114] assessed power and velocity during sets of repetitions until failure. Muscle velocity and muscle power assessment require optimal neuromuscular conditions and, as such, studies analyzing the effect of different supplements on muscular velocity and power selected a maximum of two repetitions with a submaximal load, with recovery periods of 2−5 min [117][118][119][120][121][122]. Thus, the procedure used by Ranchal-Sánchez et al [114] to assess muscle power and velocity may not be suitable to detect a potential effect of NO 3 − supplementation.…”
Section: The Effects Of Dietary Nitrate Supplementation On Weightliftmentioning
confidence: 99%
“…These results agree with those of Outlaw et al [18], whereby eight weeks of β-alanine supplementation (3.4 g/day for eight weeks) did not increase maximum strength in the leg press or bench press. In contrast, Maté-Muñoz et al [41] reported greater increases in maximal strength and power following five weeks of β-alanine supplementation. Whether β-alanine supplementation benefits maximal strength adaptations associated with resistance training still requires further investigation [36].…”
Section: Discussionmentioning
confidence: 93%